2021
DOI: 10.1111/risa.13737
|View full text |Cite
|
Sign up to set email alerts
|

Socioscientific Issues in Science Education: An opportunity to Incorporate Education about Risk and Risk Analysis?

Abstract: Socioscientific issues (SSI) concern social issues, often lacking simple solutions, that relate to science and often also risk controversies. SSIs have become an established part of science education, aiming to teach students not only about content knowledge but also about the nature of science and to offer them practice in argumentation and decision making. We performed a scoping review of the literature on SSI in science education research, in order to investigate if the topics covered would lean themselves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Thirdly, previous research has shown that teachers can be reluctant to introduce risk topics because they may not wish to reveal their own opinions (Schenk et al, 2021), or because they believe they lack strategies to work with topics that require argumentation skills (Lindahl et al, 2011). We argue that this analysis framework provides a suitable approach to justify why people have differing opinions.…”
Section: Discussion and Educational Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, previous research has shown that teachers can be reluctant to introduce risk topics because they may not wish to reveal their own opinions (Schenk et al, 2021), or because they believe they lack strategies to work with topics that require argumentation skills (Lindahl et al, 2011). We argue that this analysis framework provides a suitable approach to justify why people have differing opinions.…”
Section: Discussion and Educational Implicationsmentioning
confidence: 99%
“…Ratcliffe and Grace (2003) also support SSIs being taught in schools describing their general characteristics as those that have a basis in science, involve risk ideas, deal with incomplete information, include forming opinions, and embrace local, national or global dimensions. This approach is also supported by Schenk et al (2021) who argue that risk should be a more central part of SSI teaching and that it often includes decision-making skills. This approach would also provide contexts that embody Ravetz's (2006) notion of 'post-normal' science where risk is central.…”
Section: The Teaching Of Riskmentioning
confidence: 95%
See 1 more Smart Citation
“…On the one hand, we see opportunities for educators; because of AOT's seemingly significant upside for a wide range of judgments and decisions-including those that fall under the umbrella of risk analysis-we argue for front-lining it (and other critical reasoning skills) early and throughout a young person's education (e.g., see Baron, 1993). Unlike other work in risk education (e.g., Arvai et al, 2004;Schenk et al, 2021;Thekdi & Aven, 2021;Zint, 2001), which we agree is also essential, we are not referring here to teaching people about specific risk concepts such as judgmental biases, probability, uncertainty, or resilience. Instead, we are most interested in teaching a more fundamental mindset focused on the constructive nature of knowledge (Gurcay & Baron, 2016;Perkins, 1986) that informs many different kinds of judgments and decisions-including those involving risk analysis.…”
Section: Work To Establish Aot As a Normmentioning
confidence: 99%
“…This is because teaching and learning about STSE and SSIs may not be focused on evaluating and deciding an acceptable range of potential risks while considering benefits. Schenk et al (2021), who performed an extensive review that investigated the connection of 296 empirical SSI studies and 91 theoretical studies in science education to risk and risk analysis, found that SSI studies did not clearly involve risk assessment and management. Only a few studies introduced the notion of risk and how to analyze risks, and almost half of the studies did not mention risks at all.…”
Section: Introductionmentioning
confidence: 99%